(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Today’s world is empowered by information technology. There is nothing which is untouched with the use of technology. Education sector is also not an exception. There are lots of innovations of science that we are using in the field of education today for its betterment and Multimedia is one of them (Gupta & Chirag, 2014). In this context, an attempt has been made to see the effectiveness of IT-Enabled instructional package (ITEIP) on the science achievement among tenth class students in relation to their gender. This is an experimental study with 2×2 factorial design. 140 students of tenth standard selected through multi-stage random sampling technique were taken as a sample for the study out of which 70 students were taught through ITEIP formed Experimental group (E); and 70 students were taught through conventional method of teaching formed Control group(C).The investigators applied self-developed Achievement test in Science (Biology) to assess the achievement of the subjects. Lesson plans, and Formative tests were developed for the strategy ITEIP to carry out the teaching and learning process in all the two groups for eight weeks only. At the end of the experiment, achievement test in Science (Biology) was given to the subjects. Data were analyzed by using ANOVA and t-test to determine the performance by comparing the mean scores of all the groups. Data analysis revealed that students taught through ITEIP showed significant improvement in their achievement in science than the students taught through Conventional Method. Further, boys and girls students taught through IT-Enabled Instructional Package performed better than their counterparts. Furthermore, ITEIP appeared favorable for both boys and girls students but girls students benefitted more when they taught through ITEIP strategy. In conclusion, this study had proven that teaching through IT-Enabled Instructional Package enhances students’ achievement in Science (Biology).